Cooperative is an economic organization of farmers who have strategic positions in improving the welfare of its members and is a constitutional mandate to strengthen the national economy in anticipation of neoliberal economic development in an era of global trade. To strengthen the Village Unit Cooperatives (KUD) requires information through the development model of effective KUD organizational communication. The purposes of this research were (1) to examine the role of KUD organizational comm - Parlaungan A. Rangkuti; Sumardjo .; Amiruddin Saleh; E. Namaken Sembiring (Forum Pasca Sarjana, 2011)
Cooperative is an economic organization of farmers who have strategic positions in improving the welfare of its members and is a constitutional mandate to strengthen the national economy in anticipation of neoliberal economic development in an era of global trade.  To strengthen the Village Unit Cooperatives (KUD) requires information through the development model of effective KUD organizational communication.  The purposes of this research were (1) to examine the role of KUD organizational communication factors for performance and capacity development as agriculture economic organization, (2) to analyze the correlation of KUD organizational communication factors in associated with KUD role in efforts to improve utilization of rice milling, (3) to formulate a model of KUD organizational communication in anticipating the globalization era.  KUD sample of fair active category as the analysis unit consists of five KUD in Karawang District, they are KUD Sri Mukya, KUD Sumber Padi, KUD Warga Bakti, KUD Warga Tani and KUD Mitra Tani.  This research was designed with survey method using SEM analysis (structural equation model).  It was conducted at research location in December 2009 until March 2010. SEM analysis result showed that there was a positive and significance of the KUD performance to KUD capacity for KUD service quality improvement in the utilization of rice milling, which means testing the main hypothesis or alternative hypothesis (Ha) is accepted.   Key words: organization communication, village unit cooperatives, role of agricultural mechanization